A New Class of Higher Derivatives for Harmonic Univalent Functions Established using a Generalized Fractional Integral Operator - Ali Musaddak Delphi (Wasit Journal for Pure Sciences)
A new class of higher derivatives  for harmonic univalent functions defined by a generalized fractional integral operator inside an open unit disk E is the aim of this paper.